Legalizing the Illegal: Ethiopian Arbitration Law towards a New Jurisprudence (A Case Comment on Zem Zem PLC V. Illubabor Zone Education Department) - Tegegn, Yehualashet Tamiru (Bahir Dar University Journal of Law, 2022)
Even with its faults, arbitration is one of the most popular methods of dispute resolution. The laws for various policy justifications provide exclusionary clauses for some selected issues from the ambit of arbitration. One such area is the administrative contract. Oddly enough, the Cassation Bench renders a decision although it actually contradicts with the clear provision and spirit of the law. The author argues that the decision of the Cassation Bench is logically unsound and legally baseless; therefore, calls for revision of this position.